Relasi Pendidikan Dan Moralitas Dalam Konsumsi Media; Perspektif Filsafat Pendidikan Islam - Abror, Robby Habiba (Jurnal Pendidikan Islam, 2013)
Philosophy of Islamic education, as a branch of philosophy, is a very important role for critics, some scientists, and national generations to become good learners as well as good and high moral educators. Strong capital religion should always be accompanied by criticism that no longer exist of stagnation thinking or apologetic attitude . The role of educators. in criticizing the media is very important. Moreover, Islamic education should be paid more attention, and critical attitude towards the invasion of media. Because the (bad) influence of media can be quickly entered into our living space, into our subconscious, to act like what is desired by the latter media. Media that is out of control, must have already become a mouth piece of capitalism , or it is a capitalist regime itself.